(untitled) (Advances in Applied Biological Research, 2025)
Birth of Pakistan’s poultry industry is often attributed to the sole collaboration of Pakistan’s International Air lines- PIA with that of Canada’s Messer Shaver’s Shaver Breeding Farms. In this way, the role of the Government of Pakistan and Britian Era’s Institutions, in the late 1940s, has been overlooked altogether. In addition, the vital role played by worthy foreign and local investors e.g., Lever’s Brothers, Arber Acres Private Limited, Packages Limited, has always been undermined while unfolding the history of Pakistan poultry industry. This paper is a humble effort to put some light on hidden gems of Pakistan’s poultry industry. By particularizing their part in framing a strong poultry industry in Pakistan, it is an attempt to express our appreciations towards these pioneers.